The Effect of Economic Growth and Sanctions on Cost Stickiness in Listed Firms on the Tehran Stock Exchange - Mehdi Rezaei; Hojat Parsa; Sima Mehrabaniyan (بررسی‌های حسابداری و حسابرسی, 2018)
Cost stickiness affects the behavior of costs in different ways. In this paper, the effect of economic growth and economic sanctions on cost stickiness was investigated. The data from 117 companies of the Tehran Stock Exchange from 1996 to 2015 was selected. Multiple regression was used for hypothesis testing and to compare the coefficients during the minor and severe sanctions, the Petronaster test has been used. To examine the cost stickiness during these periods the 20-year period was divided into the boom and recession, and usual and severe sanctions periods.Cost stickiness was investigated in terms of public and administrative costs, cost of goods sold and operational costs. Results show that cost responds asymmetrically to identical sales. Economic boom affects positively costs stickiness in other words, cost stickiness raises during the economic boom. Recession has a negative effect on cost stickiness. In other words, there is no cost stickiness during recession. Although severe economic sanctions have a negative effect on cost Stickiness, the difference of cost stickiness during the usual and sever sanctions is significant in operational costs. Despite the negative impact of sanctions on cost stickiness, the difference of public and administrative costs and cost of goods sold are not statistically significant.